Autoimmunity. From Bench to Bedside (2013)
This book attempts to organize the knowledge collected by those who have extensively studied autoimmune diseases (ADs) into a comprehensive overview of how the immune system, governed by its own complex yet limited pathways, turns against self targeting distinct tissues in different conditions according to a balance determined by the genetic predisposition of the host, its gender, environmental circumstances and other co-factors that modify the outcomes of a similar pathological process (...). This book strikes a great balance at the experimental and translational intersection in presenting cutting edge views of ADs in the broader context of clinical immunology.